Semi-T-maximal sumodules - Hadi, Inaam M. A.; Elewi, Alaa A. (Iraqi Journal of Science, 2019)
Let be a commutative ring with identity and be an -module. In this work, we present the concept of semi–maximal sumodule as a generalization of -maximal submodule. We present that a submodule of an -module is a semi–maximal (sortly –max) submodule if is a semisimple -module (where is a submodule of ). We investegate some properties of these kinds of modules.